Stabilitas Termal Material Cast Iron Dan Stainless Steel Pada Proses Penyangraian Terhadap Konsistensi Cita Rasa Kopi House Blend - Subakti Subakti; Pada Mulia Raja; Zulyaden Lubis (CV. IRA PUBLISHING, 2026)
This study examines the optimization of the physical and sensory characteristics of Arabica and Robusta house blends from Sidamanik by comparing the performance of stainless steel and cast-iron roasting drums. The novelty of this research lies in mapping the influence of material heat retention on roasting profiles and flavor development in specific blend formulations. Using a factorial Completely Randomized Design (CRD), the study tested four blend ratios (100:0, 75:25, 25:75, 0:100) and analyzed parameters including moisture content, defect values, roasting curves, and sensory evaluations via hedonic and cupping tests. The results indicate that cast iron possesses superior thermal stability, significantly accelerating the attainment of the first crack compared to stainless steel. Sensorially, a 100% Arabica formulation roasted in a cast-iron machine produced a superior profile dominated by fruity and sweet characteristics. Conversely, stainless steel was found to better balance flavor complexity in the 25% Arabica and 75% Robusta blend, yielding a harmonious profile of sweet, bitter, and salty notes. These findings underscore that the selection of roasting material must be aligned with the desired blend flavor profile. Consequently, cast iron is recommended for time efficiency and consistent physical quality, whereas stainless steel remains relevant for achieving flavor equilibrium in specific house-blend formulations.